Role of miRNA in Lung Cancer-Potential Biomarkers and Therapies - Du, Xiaohong; Zhang, Jitai; Wang, Juping; Lin, Xiaoming; Ding, Feng (Current Pharmaceutical Design, 2017)
MicroRNAs (miRNAs) are small noncoding RNAs, which downregulate gene expression by repressing or degrading mRNA targets. Lung cancer (LC), together with liver and colorectal cancers are the three leading causes of cancer death worldwide, and 80% of LCs belong to non-small cell lung cancers (NSCLCs). Despite a great advancement in developing distinct and delicate tools for early diagnosis and targeted therapies over the last decade, only about 15% of the NSCLC patients eventually survived. MiRNAs are frequently dysregulated in carcinoma, including LC. Numerous lines of evidence have demonstrated various roles played by miRNAs in the development and progression of LC. In this review, we propose to summarize the current understanding of miRNAs in LC, with a particular focus on translational application of miRNAs as novel diagnostic and prognostic biomarkers and tools for treatment.
Keywords: exosome